Statutory dismissal for misconduct in Singapore-law and practices - Ang, Sheu Hoon (2013)
An ordinary man may believed that his boss has exclusive right in every manner, including hiring and firing. As business undergraduates specializing in Human Resource Management, the group aims to study the understanding of Employment Act, specifically, provisions on dismissal law, in Singapore.